2014
DOI: 10.1097/qad.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

HIV/hepatitis C virus-coinfected patients who achieved sustained virological response are still at risk of developing hepatocellular carcinoma

Abstract: HIV/HCV-coinfected patients with previous SVR may develop HCC in the mid term and long term. These cases account for a significant proportion of the total cases of HCC in this setting. Our findings reinforce the need to continue surveillance of HCC with ultrasound examinations in patients with cirrhosis who respond to anti-HCV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
1
16
0
2
Order By: Relevance
“…This is in accordance with the relationship between LSM and hepatic venous pressure gradient [20], and with a prospective study including 34 cirrhotic patients with SVR followed over 12 years, in which none developed de novo esophageal varices [18]. In addition, Roberts et al [21] demonstrated that SVR after treatment of compensated Notably, the effect of SVR on the risk of HCC has yielded diverging results [9][10][11]. In HCV monoinfected patients, Poynard et al [22] found four liver cancer in SVR, and 13 in non-SVR, a possibility that should be considered in spite of HCV eradication.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…This is in accordance with the relationship between LSM and hepatic venous pressure gradient [20], and with a prospective study including 34 cirrhotic patients with SVR followed over 12 years, in which none developed de novo esophageal varices [18]. In addition, Roberts et al [21] demonstrated that SVR after treatment of compensated Notably, the effect of SVR on the risk of HCC has yielded diverging results [9][10][11]. In HCV monoinfected patients, Poynard et al [22] found four liver cancer in SVR, and 13 in non-SVR, a possibility that should be considered in spite of HCV eradication.…”
Section: Discussionsupporting
confidence: 60%
“…Liver biopsy had been performed in 92 cases (69 %), a median time of 165 days (43-1043) before therapy. All the patients had fibrosis 4, and the median histological activity index (HAI) was 5.84 (4)(5)(6)(7)(8)(9)(10)(11)(12). The remaining 41 patients had a LSM before therapy confirming fibrosis 4.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Alcohol has an important influence on tumor development since it acts synergistically in individuals with chronic HBV and/or HCV infection [36] . HIV and HBV or HCV coinfection is an important risk factor, fostering faster liver disease progression than in individuals without HIV; if cirrhosis develops as a result, the risk for HCC is further increased [41] .…”
Section: Risk Factors and Preventionmentioning
confidence: 99%